(untitled) (Iranian Journal of Kidney Diseases, 2019)
Acute kidney injury (AKI) is a frequent and wide complication of antibiotics therapy. In the present review article, we assessed the epidemiology, pathogenesis, risk factors, and clinical manifestation of antibiotic-induced AKI. The risk factors for the occurrence of antibiotic-induced AKI include medical comorbidities, coexisting drug therapies and the dosage, and therapeutic period of antibiotics. The prognosis of antibiotic-induced AKI varies by antibiotics types. This review summarizes the clinical controversy of antibiotic treatment and the future clinical recommendations.